2023
DOI: 10.1038/s41598-023-28673-2
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter differences associated with menopausal hormone therapy in menopausal women: a DARTEL-based VBM study

Abstract: Menopausal hormone therapy (MHT) in women can reduce troublesome menopause symptoms and prevent cognitive decline. This cross-sectional study investigated the MHT-related effect on brain morphology and its association with sex hormones in menopausal women by using an optimized diffeomorphic anatomical registration through exponentiated Lie algebra (DARTEL)-based voxel-based morphometry (VBM) method. Twenty-one menopausal women without MHT (noMHT) and 20 menopausal women with MHT were included in this study. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
(77 reference statements)
1
8
0
Order By: Relevance
“… 36 Instead, the superior temporal gyrus has been proposed as one of the regions demonstrating the effects of sex hormone and age on brain volume in postmenopausal women. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“… 36 Instead, the superior temporal gyrus has been proposed as one of the regions demonstrating the effects of sex hormone and age on brain volume in postmenopausal women. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…Thirty brain regions of interest (ROIs) were selected from both hemispheres based on previous studies [ 1 , 6 , 19 , 20 , 32 ] focused on postmenopausal women, including the superior/middle/inferior frontal cortex, superior/middle/inferior temporal cortex, superior/inferior parietal lobule, lateral/medial orbitofrontal cortex, insula, hippocampus, thalamus, putamen, and amygdala. Twenty-three thalamic subnuclei (46 ROIs) were extracted for the left and right hemispheres, including the antero-ventral (AV), latero-dorsal (LD), lateral posterior (LP), ventral anterior (VA), ventral anterior magnocellular (VAmc), ventral lateral anterior (VLa), ventral lateral posterior (VLp), ventral posterolateral (VPL), central medial (CeM), central lateral (CL), paracentral (Pc), centromedian (CM), parafascicular (Pf), reuniens/medial ventral (MV-re), mediodorsal medial magnocellular (MDm), mediodorsal lateral parvocellular (MDl), lateral geniculate (LGN), medial geniculate (MGN), limitans/suprageniculate (L-SG), pulvinar anterior (PuA), pulvinar medial (PuM), pulvinar lateral (PuL), and pulvinar inferior (PuI) ( Figure 1 ) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…A similar study [ 20 ] demonstrated accelerated reduction of the hippocampal volume in postmenopausal women. Several morphometric studies [ 6 , 16 , 18 , 19 ] focusing on the effects of estrogen therapy (ET) in postmenopausal women demonstrated enhanced cognitive function that are possibly associated with improvement of the corresponding brain structure and/or connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that hormone-dependent decline in brain volume has been reported to occur in postmenopausal females, or in females receiving long term anti-estrogens ( 373 , 374 ). Conversely, post-menopausal females undergoing hormone replacement therapies display significantly larger volumes as compared to menopausal women without therapy, of several regions including superior/middle/Inferior frontal gyri, hypothalamus, inferior temporal gyrus, parahippocampal gyrus, hippocampus, cerebellar cortex, postcentral gyrus, precuneus, angular gyrus, supplementary motor area, superior occipital gyrus, and precentral gyrus ( 374 ).…”
Section: Neuroimaging In the Study Of Gender Identity And Painmentioning
confidence: 99%